Case Report: Sudden death caused by methylene chloride poisoning - Ruikai Shang; Ruikai Shang; Qiaoxin Tian; Qiaoxin Tian; Yuru Liu; Hongyu Liu; Xiangxing Zhang; Xiangxing Zhang; Mengdi Shi; Mengdi Shi; Xiangdong Jian; Xiangdong Jian; et al. (Frontiers Media S.A., 2024)
Dichloromethane is widely used as an organic solvent in aerospace, electronics, and medicine. Cases of poisoning caused by this substance are rare. Recently, we successfully treated a patient with an acute dichloromethane poisoning. During the production process, owing to pipeline leakage and lack of personal protection, the patient was poisoned by dichloromethane inhalation, fell from a height, and experienced a sudden cardiac arrest. After successful cardiopulmonary resuscitation, the patient was transferred to a local hospital for diagnosis and treatment and then to our hospital. After two visits to our hospital for systematic diagnosis and active treatment with fluid infusion, anti-infection therapy, glucocorticoids, ventilator-assisted respiration, chest strap fixation, and nutritional support, the patient achieved clinical recovery.